Examining the use of pearson activeteach and myenglishlab in teaching English for general purposes (EGP): a classroom action research - Gufron, Gufron; Md Zamin, Ainul Azmin (International Journal of Social Science and Human Research, 2024)
This classroom action research study aims to delve into the experiences of students in learning English for General Purposes (EGP) by utilizing Pearson MyEnglishLab and ActiveTeach, two online teaching and learning tools developed by Pearson Education. Through a mixed-method approach that combines quantitative and qualitative research methods, the study investigates the effects of these tools on student engagement and learning outcomes. Over the course of one semester, the researchers observed the learning process, conducted interviews with students, and administered questionnaires to gather comprehensive data. The analysis of the collected data reveals that teaching EGP with ActiveTeach and Pearson MyEnglishLab yields significantly more engaging and impressive outcomes in comparison to traditional teaching methods. These online tools offer various benefits, including the consolidation of teaching materials within a single application. Students appreciate the convenience and accessibility of having reading passages, listening audio, and assessments readily available in one platform, thereby streamlining their learning experience. Overall, this study underscores the positive impact of online tools, specifically Pearson MyEnglishLab and ActiveTeach, on EGP classrooms. The findings highlight the potential of these tools to enhance student experiences, foster engagement, and promote effective language learning. By embracing digital platforms, educators can harness the benefits of technology to optimize the teaching and learning process in EGP contexts.